2011
DOI: 10.1063/1.3604012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition-assembled graphene field-effect transistor on hexagonal boron nitride

Abstract: We investigate key electrical properties of monolayer graphene assembled by chemicalvapor-deposition (CVD) as impacted by supporting substrate material. Graphene field-effect transistors (GFETs) were fabricated with carbon channel placing directly on hexagonal boron nitride (h-BN) and SiO 2 , respectively. Small-signal transconductance ( m g ) and effective carrier mobility ( eff  ) are improved by 8.5 and 4 times on h-BN, respectively, as compared with that on SiO 2 . Compared with GFET with exfoliated graph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…In Teng's work, they reported the mobility (μ) of the graphene film was 600 cm 2 V À 1 s À 1 [15]. Well, Edwin Kim prepared graphene films on Cu foils, and the mobility (μ) was 1200 cm 2 V À 1 s À 1 [16]. However, the experimental study on the carrier transport properties of bilayer graphene was rarely reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In Teng's work, they reported the mobility (μ) of the graphene film was 600 cm 2 V À 1 s À 1 [15]. Well, Edwin Kim prepared graphene films on Cu foils, and the mobility (μ) was 1200 cm 2 V À 1 s À 1 [16]. However, the experimental study on the carrier transport properties of bilayer graphene was rarely reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we identify conditions at which the first moiré miniband is separated from the rest of the spectrum by either one or a group of three isolated mini Dirac points and is not obscured by dispersion surfaces coming from other minibands. In such cases the Hall coefficient exhibits two distinct alternations of its sign as a function of charge carrier density.PACS numbers: 73.22.Pr,73.21.Cd, Recently, it has been demonstrated that the electronic quality of graphene-based devices can be dramatically improved by placing graphene on an atomically flat crystal surface, such as hexagonal boron nitride (hBN) [1][2][3][4][5][6][7]. At the same time, graphene's electronic spectrum also becomes modified, acquiring a complex, energydependent form caused by incommensurability between the graphene and substrate crystal lattices [8][9][10].…”
mentioning
confidence: 99%
“…It was surprising that small-signal transconductance and effective carrier mobility were improved by 8.5x and 4x, respectively, on h-BN/SiO 2 as compared with that on SiO 2 /Si. [ 148 ] Novoselov et al indicated that the atomically thin h-BN layer could act as a non-defective dielectric layer with a high puncture fi eld, which has potential for applications in tunnel devices and FETs with a high carrier density in the conducting channel. [ 149 ] According to the theoretical study of Schwingenschlögl et al, the strong interaction between boron atoms and carbon atoms led to the strong interaction between single-layer graphene and h-BN, which resulted in the inequivalence of the two carbon atoms of the graphene unit cell.…”
Section: Reviewmentioning
confidence: 99%